Beyond weight loss in nonalcoholic fatty liver disease: the role of carbohydrate restriction. Issue 4 (July 2021) - Risi, Renata; Tozzi, Rossella; Watanabe, Mikiko
Abstract : Purpose of review: The low fat diet (LFD) is currently the first choice to treat nonalcoholic fatty liver disease (NAFLD) alongside with physical activity. However, low carbohydrate diets (LCDs) and ketogenic diets have gained attention lately, thanks to their favourable impact in reducing intrahepatic triglyceride content. We therefore aimed at providing an update on recent evidence evaluating the hepatoprotective effects of such dietary interventions. Recent findings: Novel findings confirmed previous evidence by showing beneficial effects on liver fat content reduction for both LFDs and LCDs. The further restriction of carbohydrates to less than 50 g/day, usually leading to ketosis, confirmed to produce an improvement in NAFLD, with very low-calorie ketogenic diets possibly proving particularly beneficial thanks to the significant weight loss that can be obtained. Summary: Most of the latest evidence shows that carbohydrate restriction plays a fundamental role in the modulation of lipid metabolism leading to similar efficacy in improving NAFLD compared with LFDs. The hepatoprotective role of carbohydrate restriction appears to be boosted when ketogenesis is induced, when the total calorie intake is extremely reduced, or, possibly, when dietary interventions have reduced content in free sugars, making such interventions valuable tools to deal with NAFLD.